PELATIHAN PENULISAN ARTICLE DAN SUBMIT OPEN JOURNAL SYSTEM (OJS) UNTUK MAHASISWA TINGKAT AKHIR - Waldelmi, Idel; Aquino, Afvan; Listihana, Wita Dwika (CV. Alina, 2024)
The purpose of the implementation of this service is expected to be able to increase knowledge, understanding and confidence for students to know further and more widely in compiling scientific papers and entering the journal system (OJS). The implementation of this training was carried out online by zoom and was attended by 77 participants out of 160 participants who registered. The results of the implementation of this service obtained results which stated that the level of knowledge, understanding and confidence of the participants to be able to write scientific papers was very high, and the participants were very enthusiastic in participating in this training.